Border adjustments under unilateral carbon pricing: the case of Australian carbon tax - Mahinda Siriwardana; Sam Meng; Judith McNeill (Journal of Economic Structures, 2017)
Abstract In the absence of a global agreement to reduce emissions, Australia adopted a carbon tax unilaterally to curb its own emissions. During the debate prior to passing the carbon tax legislation in 2011, there were concerns about the challenge that Australia’s emissions-intensive and trade-exposed (EITE) industries may face in terms of decreasing international competitiveness due to the unilateral nature of the tax and hence the potential for carbon leakage. In order to address these concerns, this paper explores possible border adjustment measures (BAMs) to complement the domestic carbon regulation in Australia using the multi-sector computable general equilibrium approach. We consider four border adjustments: border adjustments on imports based on domestic emissions; border adjustments on exports via a rebate for exports; a domestic production rebate; and full border adjustment on both exports and imports. We compare the numerical simulation results of these scenarios with a no border adjustments scenario from the standpoint of welfare, international competitiveness and carbon leakage. The key finding is that BAMs have a very small impact on the overall economy and on EITE sectors. In other words, the different BAMs have minimal impact on the outcomes of carbon pricing policy. This finding is consistent with studies for EU, USA, Canada and other countries. Hence, we conclude that the border adjustments are ineffective instruments to safeguard EITE industries in Australia.